ARMENIAN STUDIES OF SOVIET EVERYDAY LIFE: A HISTORIOGRAPHICAL REVIEW - Zamgaran, Gagik Agasievic; Hacatran, Karen Gamletovic; Sukiasan, Amo Karenovic (History, Archeology and Ethnography of the Caucasus, 2026)
The crisis of the humanities that began in the late 19th century triggered a search for new methodological and epistemological approaches to historical study throughout the 20th century. This evolution led to the emergence of new historiographical directions, one of which is the history of everyday life. Since the 1970s and 1980s, the history of everyday life has established itself as an independent branch of historical knowledge, gaining widespread recognition in Western, post-Soviet, and particularly Russian historiography. Amidst the enduring interest in this paradigm, discussions regarding the formation of an Armenian scholarly school dedicated to the history of everyday life have become increasingly relevant within Armenian historical thought. The purpose of this article is to introduce the broader scientific community to research initiatives focused on Soviet everyday life within Armenian historiography. In the context of studying Soviet-era Armenian society, this paper provides a generalized historiographical review of the most notable works in this field. Specifically, it highlights the methodological challenges addressed by Armenian specialists: defining the subject matter of the history of everyday life; establishing methodological foundations for research; developing approaches for the heuristic analysis of diverse source materials. Using qualitative content analysis, the article outlines the primary thematic areas of Armenian research, covering various aspects of social life in Soviet Armenia. Based on the current state of historiography in the region, the paper also examines the relevance and developmental prospects of this field. The history of everyday life may be considered a precursor to anthropologically oriented research in Armenian historiography, relying on interdisciplinary principles. Its rich methodological toolkit and diverse thematic scope, focusing not only on political history but on the broader spectrum of human activity, create new avenues for studying the Soviet past. Consequently, the article concludes that the history of everyday life, as a conceptual framework, offers new opportunities for a more comprehensive study of the history of Soviet Armenia.
Keywords: Armenian historiography; history of everyday life; oral history; Soviet Armenia; Soviet everyday life; historical methodology